Kidult (nie tylko) językowy - Wileczek, Anna (Postscriptum Polonistyczne, 2020)
The article aims to analyse the phenomenon of kidult, that is, participating in life and culture combining elements that are typical for both children (kids) and adults. Postmodern cultural practices that glorify youth, flexibility, communicative strategies based on individualization, freedom of language, humour and effective communication are described in the article. The aim is to create an attractive and original utterance, while language rules are of secondary importance. Kidult as a conglomerate of many styles and sociocultural patterns seems to be a fashionable element of contemporary lifestyle.